Tellurite-Exposed Escherichia Coli Exhibits Increased Intracellular ?-Ketoglutarate - Vasquez-Guzman, C (2012)
The tellurium oxyanion tellurite is toxic to most organisms because of its ability to generate oxidative stress. However, the detailed mechanism(s) how this toxicant interferes with cellular processes have yet to be fully understood. As part of our effort to decipher the molecular interactions of tellurite with living systems, we have evaluated the global metabolism of ?-ketoglutarate a known antioxidant in . Escherichia coli. Tellurite-exposed cells displayed reduced activity of the KG dehydrogenase complex (KGDHc), resulting in increased intracellular KG content. This complex s reduced activity seems to be due to decreased transcription in the stressed cells of . sucA, a gene that encodes the E1 component of KGDHc. Furthermore, it was demonstrated that the increase in total reactive oxygen species and superoxide observed upon tellurite exposure was more evident in wild type cells than in . E. coli with impaired KGDHc activity. These results indicate that KG may be playing a pivotal role in combating tellurite-mediated oxidative damage. © 2012 Elsevier Inc.